Two roads diverged: An alternative perspective on the EASI model - MELIA, Nadhilla Velda (Institutional Knowledge at Singapore Management University, 2021)
Research on the interpersonal effect of anger expressions on others’ concessionary behaviour has found conflicting results about whether anger expressions increase or decrease concessionary behaviour. The Emotions as Social Information (EASI) model (Van Kleef, 2009, 2014) proposed that these conflicting findings can be resolved by looking at inferential and affective processes. Specifically, anger expressions increase concessionary behaviour via inferential processes but decrease concessionary behaviour via affective processes. However, previous research has mainly focused on dominance-related inferences and reciprocal anger reactions. I propose that the relationship between anger expressions and concessionary behaviour is determined by the type of inferential and affective processes, and not just whether inferential or affective processes are occurring. I explore other inferential processes, such as affiliation-related inferences, and other affective processes, such as complementary fear reactions, together with dominance-related inferences and reciprocal anger reactions, as possible mediators of the relationship between anger expressions and others’ concessionary behaviour. I also propose that the relative influence of these mediators depends on the perceived appropriateness of the anger expression and investigate the proposed model in a transgression setting. I found support for the mediating effect of dominance-related inferences and partial support for the mediating effect of reciprocal anger reactions, but not the other mediators. I also found partial support for the moderating effect of a counterpart’s transgression role on the relationship between anger expressions and perceived appropriateness. I also did not find any moderating effects of perceived appropriateness. Implications of these findings and future research plans for further testing of the EASI model are discussed.